Activity Study of Absorbent Prepared from CaO/CaSO4/Coal Fly Ash for SO2 Removal at Low Temperatures. - E, H Raymond Ooi; K, T Lee; Mohamed, A R (2004)
This study presents findings from an experimental investigation of the influences of several factors on the desulfurization capacity of absorbent prepared from coal fly ash, CaO, and CaSO4. The absorbent was synthesized using hydrothermal reaction while the sulfation experiments were performed in a fixed-bed reactor under isothermal conditions at low temperature.